Magnetic point contact in ferromagnetic semiconductor (Ga,Mn)As - Figielski, T.; Wosinski, T.; Morawski, A.; Pelya, O.; Makosa, A.; Dobrowolski, W.; Wrobel, J.; Sadowski, J.; Jagielski, J.; Ratajczak, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
We show that narrow constrictions, a few hundred nanometers wide, in ferromagnetic semiconductor (Ga,Mn)As layer exhibit large spin-related magnetoresistance. Moreover, we demonstrate that application of oxygen-ions implantation, instead of chemical etching, is much better method of tailoring nanometer-size circuits in (Ga,Mn)As suitable for future spin electronics.